STUDI KORELASI: PENGGUNAAN BAHASA DAERAH (KARO) DENGAN STRATIFIKASI SOSIAL PADA KELUARGA JEMAAT GBKP KLASIS MEDAN-KP.LALANG - ADRIAN JAN PUTRA TARIGAN (Departemen Sosiologi Universitas Sumatera Utara, 2013)
Regional language is a language used by people in certain limited geographic areas within the territory of a state. In terms of quantity the amount of use of local languages ​​in Indonesia has decreased, particularly in the church GBKP Klasis Medan-Kp.Lalang. Social class may affect the use of the local language when communicating with family Karo, communicating with fellow ethnic Karo, as well as communicate with different ethnicities. The study found there is a significant correlation between the amount of revenue the Karo district of language as communication between parents and the child, the child to his brother / sister / brother, the ethnic neighbors, to fellow ethnic family, the neighbors of different ethnic groups, the large families of different ethnic groups, and no significant relationship at the time of communication between husbands and wives, and when communicating with other members of the congregation GBKP. So also in the residential areas that have a significant correlation when the communication between husbands and wives, the children to the parents, the children to the brother / sister / brother, his fellow church members GBKP, the ethnic neighbors, extended family fellow ethnic, ethnically different neighbors, the family of different ethnic groups, and no significant relationship at the time of communication between parent to child. Keywords: THE USE OF LANGUAGE (Karo), STRATIFICATION SOCIAL